The capital asset pricing model in the 21st century : analytical, empirical, and behavioral perspectives - Levy, Haim (Cambridge University Press, 2012)
"Project Theory and the classical models in finance (e.g., the CAPM) seemingly contradict each other, creating a teachin and a research dilemma to professors in finanace and econommics, This tension is particualrly strong for professors who teach both the CAPM and behavioral finance. This book bridges between Prospect Theory and the Classical Models in finance showing that there is no contradictions between them"-- Provided by publisher